Edukasi Pemeriksaan Inspeksi Visual Asam Asetat (IVA) pada Wanita Usia Subur (WUS) di Wilayah Kerja Puskesmas Tanah Luas Kabupaten Aceh Utara - Nurmila, Nurmila; Elizar, Elizar; Putri, Hendrika Wijaya Kartini (Universitas Baiturrahim, 2024)
Cervical cancer is the fourth most common cancer affecting women worldwide. Prevention and screening are by far the most effective modalities for reducing health care burden and mortality from cervical cancer. In Indonesia, cervical cancer is the second largest cancer disease after breast cancer. Many women are still unable to detect cervical cancer at an early stage for various reasons. Personal, social, cultural and structural factors are the most important barriers to cervical cancer screening. The problem-solving method used is education through presentations about IVA examinations by distributing leaflets and posters and carrying out IVA examinations. When carrying out community service activities, there were 30 women of childbearing age who attended. Community service activities carried out for two days in the Tanah Luas Community Health Center Work Area, North Aceh Regency, there was an increase in the knowledge of the community service target audience regarding IVA Examination education, the pretest evaluation of targets who had good knowledge was 40% and in the posttest evaluation good knowledge was 90%. The entire target audience (30 WUS) actively participated in the IVA examination. It is important for health workers to continue to provide information and education about the importance of VIA examinations as an effort to detect cervical cancer early.